Cloning, expression and purification of a gene encoding CFP-10 and ESAT-6 protein of Mycobacterium tuberculosis in pET SUMO plasmids as Vaccine Candidates - Fihiruddin Fihiruddin; Nurul Inayati; Lalu Srigede; Siti Zaetun; Lalu Unsunnhidal; Muhammad Nazil Shaleh (Jurnal Penelitian Pendidikan IPA, 2026)
The Bacillus Calmette-Guerin vaccine did not show consistent results in preventing tuberculosis, with an effectiveness ranging from 0% to 80%. More effective proteins are needed as vaccine candidates to eliminate tuberculosis. Culture filtrate proteins 10-kDa(CFP-10) and Excretory Antigen Target 6-kDa(ESAT-6) demonstrated very strong antigenicity against T and B cells. These proteins are secreted during the early phase of infection and could potentially be used for vaccine candidates. This study aims to clone and express the CFP-10 and ESAT-6 proteins on the pET SUMO Plasmid. PCR with specific primers was used to amplify the genes encoding CFP-10 and ESAT-6 proteins. The PCR products were cloned into pET SUMO plasmids for transformation into competent cells E.coli BL21(DE3). Recombinant protein expression was induced in LB medium using 1 mM IPTG. The yield of recombinant proteins was visualized by SDS-PAGE and western blotting using an Anti-HisTaq Antibody. PCR results showed the target gene sizes to be 304 bp (CFP-10) and 291 bp (ESAT-6). SDS-PAGE and Western blotting revealed proteins at 22kDa (CFP-10) and 18kDa (ESAT-6). The genes encoding the CFP-10 and ESAT-6 proteins of M. tuberculosis have been successfully cloned into the pET SUMO plasmid and expressed in E. coli BL21(DE3) with molecular weights corresponding to the target genes.